Comparative study on the microbial adhesion to preveneered and stainless steel crowns - Waleed M Bin AlShaibah; Fatma A El-Shehaby; Norhan A El-Dokky; Ala'a R Reda (Wolters Kluwer Medknow Publications, 2012)
Context: The extensive plaque formation on dental restorations may contribute to secondary caries or periodontal inflammation. Therefore, it is important to know how different types of dental restorations may prevent or promote the accumulation of microorganisms. Aims: The aim of this in vivo study was to evaluate the adhesion of Streptococcus mutans to preveneered and stainless steel crowns (SSCs) and to evaluate the effects of these restorations on the gingival health and oral hygiene. Materials and Methods: Twenty patients (age 3-5 years) were selected from the outpatient clinic of the pedodontics department, Faculty of Oral and Dental Medicine, Cairo University. The selected patients had (dmf) index for primary dentition ≤4, including lower right and left first primary molars. Each tooth was pulpotomy-treated and restored with either type of crowns (split-mouth technique). Then, ten swabs from the buccal mucosa, preveneered crown, and SSC surfaces were taken from each patient. Also, the gingival index (GI) and oral hygiene index (OHI-S) were measured at different times during the study. Mitis Salivarius Bacitracin agar (MSBA) was used as a selective medium for S. mutans growth. MSBA plates were taken in candle jar and incubated aerobically in 37°C for 48 h. Finally, bacteria were counted and expressed in colony forming unit (CFU). Results: After 1, 2, and 4 weeks, mucosa and crown swabs of preveneered crown showed statistically significant higher mean CFU counts than SSC. Through the whole study period, the two restorations revealed a statistically significant decrease in mean CFU counts. Also, there was a statistically significant positive (direct) correlation between OHI-S, GI, and S. mutans counts on both restorations. Conclusions: The adhesion of S. mutans to preveneered crowns was higher than to SSC. Full mouth rehabilitation led to significant decrease in S. mutans count in the short term. An increase in S. mutans counts is associated with an increase in OHI-S and GI.